Hubungan Pengetahuan dan Pekerjaan Ibu dalam Memberikan ASI Eksklusif di Puskesmas Rambah Samo I - Fahmi, Yuyun Bewelli (Jurnal Martenity and Neonatal, 2019)
Breast feeding has many benefits because it is a food that contains balanced nutrition for babies, and contains immunity that can reduce the risk of babies contracting the disease. The type of research in this study is quantitative with analytic methods, with a cross sectional design. This population is all mothers who have babies over 6 months at the time of the study. The purposive sampling technique used was 130 people. The study was conducted during July 2018. Data analysis used statistical tests with chi square. Based on the results of the study, it was found that there was a relationship between knowledge and failure of mothers to provide exclusive breastfeeding. The results of chi square test p> 0.005 (p = 0.04), there was no relationship between work and maternal failure in giving exclusive breastfeeding obtained p> 0, 05 (p = 0.65). After doing this research, it is expected that health workers always improve the quality of health services by providing counseling about the importance of giving exclusive breastfeeding to their babies until the age of 6 months.